Risk factors for inhibitor development in severe hemophilia A. Issue 168 (August 2018) - Garagiola, Isabella; Palla, Roberta; Peyvandi, Flora
Abstract: Although significant advances in hemophilia treatment have improved patient outcomes and quality of life, one of the greatest complications in severe hemophilia A is the development of anti-Factor VIII (FVIII) antibodies that inhibit FVIII activity in almost 30% of previously untreated patients (PUPs). Inhibitors make very difficult the management of patients and increase their morbidity and mortality reducing drastically their quality of life. Numerous studies have investigated the mechanisms leading to the development of FVIII inhibitors. However, the etiology of their onset is complex and not yet fully understood. Inhibitors develop from a multicausal immune response involving both genetic (unmodifiable) and environmental (modifiable) factors. F8 gene mutations are the most important genetic risk factor, with null mutations being associated with the highest risk of inhibitor development. Immune response genes (e.g. the human leukocyte antigen complex) and proteins (e.g. cytokines) were studied without any strong confirmation of their role in modulating of inhibitor development. Type of FVIII product is the most important modifiable risk factor. The plasma-derived products containing von Willebrand factor were recently suggested to determine a lower incidence of inhibitor development than recombinant products in PUPs, in the first 50 exposure days (EDs). Other environmental factors including, age at first treatment, treatment intensity and the danger signal effect (surgery, severe bleeds, vaccinations and infections) has also been postulated as an explanation for environment-related inhibitor risk. This review reports the current knowledge on genetic and environmental risk factors on inhibitor development in patients with severe hemophilia A. Highlights: Almost 30% of patients with severe hemophilia A develop anti-factor VIII inhibitors. Both genetic and environmental factors contribute to the risk of inhibitor formation. The most important genetic risk factor is the type of F8 gene mutation. The most important environmental risk factors are type of FVIII products and treatment intensity. More robust studies are needed to investigate other potential risk factors.